Family and individual variables associated with young Filipino children's numeracy interest and competence. (23rd November 2017) - Cheung, Sum Kwing; Yang, Xiujie; Dulay, Katrina May; McBride, Catherine
Abstract : Children's early numeracy outcomes set the foundation for mathematics learning in their future school years. This study examined how different family and individual variables were associated with the numeracy interest and competence of disadvantaged young children in the Philippines. The numeracy and literacy skills of 673 children living in low‐middle income communities were tested. Their parents were also asked to complete a questionnaire on demographics, their home numeracy practices, attitudes about numeracy learning, and children's numeracy interest. Structural equation modelling analyses showed that children's numeracy interest was linked with their parents' practices and attitudes. Children's numeracy competence, on the other hand, was related to their gender, age, socioeconomic status, and literacy abilities. These findings suggest that family and individual variables might play different roles in disadvantaged children's early numeracy development. Moreover, parents can be encouraged to make effective use of home numeracy experiences to promote their children's numeracy competence. Statement of contribution What is already known on this subject? In developed countries, home environment is occasionally found to link with early numeracy development. Some individual variables are also found to play significant roles in early numeracy development. What does this study add? Among young Filipino children from disadvantaged backgrounds, home environment is related to numeracy interest. Family socioeconomic status plays a significant role in early numeracy competence. Early literacy and numeracy skills are interrelated with each other.